2016
DOI: 10.1016/j.dyepig.2016.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, chemosensing properties and logic behaviour of a novel ratiometric 1,8-naphthalimide probe based on ICT and PET

Abstract: A novel fluorescence sensing 1,8-naphthalimide designed on the "receptor 1-fluorophorespacer-receptor 2 " model is synthesized and investigated. The novel probe comprising aminotriazole and hydroxyphenyl substituents is capable to operate simultaneously via ratiometric ICT and PET signalling mechanism. The synthesized compound shows excellent signalling properties towards protons, hydroxyl anions and Cu 2+ ions. Due to the remarkable fluorescence changes in the presence of these analytes the system is able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…[15][16][17][18] Several 1,8-naphthalimide chemosensors have been developed for detection of cations, anions, and small polar molecules. [19][20][21][22] However, 1,8-naphthalimide based chemosensors with selective response to Ba 2+ remain underdeveloped. 9,23 Selective barium sensing has been demonstrated by a relatively small number of instructive fluorescent chemosensors.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Several 1,8-naphthalimide chemosensors have been developed for detection of cations, anions, and small polar molecules. [19][20][21][22] However, 1,8-naphthalimide based chemosensors with selective response to Ba 2+ remain underdeveloped. 9,23 Selective barium sensing has been demonstrated by a relatively small number of instructive fluorescent chemosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, excited electron transfers from ICT state to the ground state, which produces a change in D–A molecule emission . Based on the charge transfer, PET and ITC are common mechanisms for designing fluorescence switches . By using PET and ICT fluorescent probes 1,8‐naphthalimide as energy donor, a series FRET systems were realized .…”
Section: Resultsmentioning
confidence: 99%
“…Then samples were incubated at 37 °C for three hours using shaker incubator. In the next step, samples were based probes, ion sensors, cellular imaging, and DNA targeting [57][58][59][60][61][62]. In addition, recent reports have been shown that polycarbonate based urethanes have great blood compatibility [34][35][36][37].…”
Section: Biocompatibility Testsmentioning
confidence: 99%